MORPHOTECTONIC ANALYSIS AT TANIMBAR TRENCH AS A BASE FOR GAS PIPE LAYING BETWEEN MASELA BLOCK AND SELARU ISLAND, MOLUCCAS PROVINCE - Ediar Usman; Priatin Hadi Widjaja (BULLETIN OF THE MARINE GEOLOGY, 2012)
The study area is located at Masela Block and its surrounding, Moluccas Province. Result of the deep sea measurement and global data conversion provide description of three dimensions around the track lines area. This result is overlay with seismic data, that can give morphotectonic implication between Asian and Australian Plates. Track lines of MGI-2010-MSL-1, 2 and 3 show that the profile of the sea floor, form the high morphology which represents the volcanic islands. It forms west – east direction of fold-thrust belt non-volcanic outer Banda arc. The southern part trench of the Australian Continent reflected the platform system and undulation morphology. The sea floor profile ( VE 1:5 ) show that the slope profile ranges between 0º and 8º. Furthermore, the morphology of the sea floor can be classified as a relatively flat slope. Due to this condition, this area may be used for gas pipe laying along 146 km distance, between the Well of Abadi 1 at the Masela Block and Selaru Island at south Tanimbar Islands. Keywords: sea depth, sea floor morphology, seismic profile, tectonic, Masela Block Daerah penelitian terletak di Blok Masela dan sekitarnya, Provinsi Maluku. Hasil pengukuran kedalaman laut dan konversi data global diperoleh gambaran tiga dimensi di sekitar jalur lintasan. Hasil ini kemudian ditumpangtindihkan dengan data seismik, sehingga dapat memberikan gambaran morfologi dan implikasi tektonik antara Lempeng Asia dan Australia. Pada Lintasan MGI-2010-MSL-1, 2 dan 3, menunjukkan profil kedalaman dasar laut membentuk morfologi tinggian yang mewakili pulau-pulau vulkanik. Kondisi ini membentuk suatu jalur punggungan lipatan sesar naik non vulkanik Busur Luar Banda berarah barat – timur. Di bagian selatan palung, mewakili Benua Australia; menunjukkan suatu sistem paparan dan morfologi undulasi Penampang dasar laut (VE 1 : 5) memperlihatkan bahwa kemiringan lereng berkisar antara 0º dan 8º. Selanjutnya morfologi dasar laut ini dapat diklasifikasikan sebagai lereng yang relative landai. Berdasarkan kondisi ini daerah ini kemungkinan dapat digunakan untuk peletakan pipa gas sepanjang 146 km, antara Sumur Abadi 1 di Blok Marsela dan Pulau Selaru di sebelah selatan Pulau Tanimbar. Kata kunci: kedalaman laut, morfologi dasar laut, enampang seismik, tektonik, Blok Masela